Communication Modeling of Solar Home System and Smart Meter in Smart Grids - S. M. Suhail Hussain; Ashok Tak; Taha Selim Ustun; Ikbal Ali (IEEE Access, 2018)
The future energy networks are envisioned to be green and clean with high penetration of renewable energy-based generators. The most promising type is solar energy which has immense potential around the globe. Solar home systems (SHSs) with rooftop solar panels are proliferating in urban cities as well as in distant rural areas. Possible interaction of SHS with utility grid will result in dynamic power flow which is a huge challenge for power utility authorities and consumers. The smart meters (SMs) are being deployed to make this possible through bi-directional energy and information exchange. In order to address this need, this paper develops the communication models of SHS and SM based on the IEC 61850 standard. These models provide standardized approach to these technologies and facilitate a series of functionalities, such as power flow control, demand response, and other ancillary services, using configured message exchange. The detailed models, their use cases and the messages are studied in detail. Furthermore, extensive simulations are run with riverbed modeler to investigate the dynamic performance. IEC 61850-based models of SHS and SM are implemented, message frames are developed according to use cases, and the functionalities mentioned earlier are run as scenarios. Finally, the performances of different communication technologies have been analyzed to estimate their adequacy for smart grid implementations.